AquaDualPark Study - Effects of Aquatic and Land-Based Dual-Task Exercise Program on Motor and Cognitive Functions of People With Parkinson's Disease: Protocol for a Randomized Clinical Trial. - Silva, Adriano Zanardi da; Israel, Vera Lúcia (Health Services Insights, 2025)
Background: Exercise-based interventions, particularly dual-task training (DT), have been increasingly recognized as effective strategies for improving cognitive, motor, and functional capacities in individuals with Parkinson's disease (PD). This study presented a protocol for a randomized controlled trial (RCT) designed to evaluate and compare the effects of land and aquatic-based single-task (ST) and dual-task (DT) training on physical and cognitive outcomes in individuals with PD. The present study aims to describe the protocol of 4 different physical exercise programs, including single-task and dual-task exercises on land and in the aquatic environment, and their potential impact on the cognitive, motor, functional, and quality of life capacities of people with Parkinson's disease. Methods: This randomized controlled trial (RCT) involved individuals with PD who were randomly assigned to 1 of 4 intervention groups: (i) Land Single-Task (LST), (ii) Land Dual-Task (LDT), (iii) Aquatic Single-Task (AST), and (iv) Aquatic Dual-Task (ADT). Participants in each group underwent a 12-week exercise program with standardized volume, frequency, and intensity. The interventions focused on improving cognitive and motor functions, balance, dynamic gait, fear of falling, and quality of life (QoL). A battery of validated assessments was used, including the MoCA, SCOPA-COG, TUG, FTSST, Mini-BEST, DGI, ABC, and PDQ-39, administered at baseline, post-intervention, and at a 12-week follow-up. Objectives: This study aimed to investigate whether dual-task training, particularly in the aquatic environment, offered superior benefits over single-task training in improving cognitive, motor, and functional abilities in individuals with PD. Additionally, the study explored the potential of the aquatic environment to provide unique stimuli that enhance neuroplasticity, balance, and overall mobility. Conclusions: This protocol outlined a structured approach to evaluating the effectiveness of land and aquatic-based exercise interventions in individuals with PD. The findings from this study will contribute to the development of evidence-based guidelines for exercise prescription in PD, emphasizing the role of aquatic environments in therapeutic interventions.